2019
DOI: 10.1021/acsami.9b14412
|View full text |Cite
|
Sign up to set email alerts
|

Charge Separation in Epitaxial SnS/MoS2 Vertical Heterojunctions Grown by Low-Temperature Pulsed MOCVD

Abstract: The weak van der Waals bonding between monolayers in layered materials enables fabrication of heterostructures without the constraints of conventional heteroepitaxy. Although many novel heterostructures have been created by mechanical exfoliation and stacking, the direct growth of 2D chalcogenide heterostructures creates new opportunities for large-scale integration. This paper describes the epitaxial growth of layered, p-type tin sulfide (SnS) on n-type molybdenum disulfide (MoS2) by pulsed metal–organic chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Nevertheless, to date there are limited studies on such interlayer optical and electronic responses. [254][255][256][257][258] Furthermore, the highly anisotropic electrical and optical properties in MMCs integrated with 0D (quantum dots) or 1D organic and/or inorganic and perovskite semiconductor materials could open up a new path for next-generation electronic applications. Overall, the very recent exciting achievements in the field of few-layer MMCs showed a great potential for their application in next-generation electronic, optoelectronic, and emerging nanophotonics, including valley electronics, solar cells, sensors, and nonlinear optical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to date there are limited studies on such interlayer optical and electronic responses. [254][255][256][257][258] Furthermore, the highly anisotropic electrical and optical properties in MMCs integrated with 0D (quantum dots) or 1D organic and/or inorganic and perovskite semiconductor materials could open up a new path for next-generation electronic applications. Overall, the very recent exciting achievements in the field of few-layer MMCs showed a great potential for their application in next-generation electronic, optoelectronic, and emerging nanophotonics, including valley electronics, solar cells, sensors, and nonlinear optical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The energy dispersive X‐ray analysis (EDX) result showed that the width of the interfacial transition region between Sb 2 Te 3 and Bi 2 Te 3 is below 3 nm. This work demonstrates that the solvothermal method is a facile alternative to the widely used vapor‐phase methods (e.g., CVD, [ 254,255 ] PVD, [ 256 ] and metal‐organic chemical vapor deposition (MOCVD) [ 257 ] ) for producing 2D heterojunctions. Wang et al [ 258 ] synthesized a novel atomic‐scale heterojunction between ultrathin g‐C 3 N 4 nanosheets (ug‐CN) and monolayer Bi 2 WO 6 nanosheets (m‐BWO) using a hydrothermal reaction.…”
Section: The Preparation Of 2d Materialsmentioning
confidence: 99%
“…MOCVD is appealing for the large‐scale production of 2D materials films with thickness and doping control. [ 257,390,391 ] The carrier gas passes through the organometallic precursors in a typical MOCVD synthesis of 2D materials (e.g., stainless steel cylindrical bubbler). The saturated vapor of the precursor is brought into the reaction chamber and mixed with other reaction gases.…”
Section: The Preparation Of 2d Materialsmentioning
confidence: 99%
“…In the loaded model, the electrons can quickly transfer across the substrate materials (e.g., MXenes and graphene) to 0D, 1D, or 2D SnS nanostructures for remarkably improved performances. [28,[113][114][115][116][117][118][119] In the following, some typical examples including 0D, 1D, and 2D SnS nanostructures, are introduced to demonstrate the features of SnS-based heterostructures in a loaded model to highlight the promising applications. [28,114,118,119] Hybriding 0D SnS with other materials in a loaded model usually integrate the advantages of both individual constituents and overcome their individual shortcomings, such as serious agglomeration.…”
Section: Loaded Modelmentioning
confidence: 99%
“…[28,[113][114][115][116][117][118][119] In the following, some typical examples including 0D, 1D, and 2D SnS nanostructures, are introduced to demonstrate the features of SnS-based heterostructures in a loaded model to highlight the promising applications. [28,114,118,119] Hybriding 0D SnS with other materials in a loaded model usually integrate the advantages of both individual constituents and overcome their individual shortcomings, such as serious agglomeration. In 2020, Liu et al [118] designed a new heterostructure .…”
Section: Loaded Modelmentioning
confidence: 99%